Newcomers and social and health pressures in Franco-Manitoban communities: Overview of avenues of research and preliminary considerations - Bahi, Boniface (Canadian Issues, 2008)
This article outlines theoretical considerations and preliminary data for a research project undertaken at the request of the research office at the Collège universitaire de Saint-Boniface in Winnipeg, with the support of the Corporation Catholique de la Santé du Manitoba. The Corporation's "Étude d'évaluation stratégique sur l'intégration des médecines alternatives à la médecine officielle (2006-2009)" seeks to build the capacities of public medical institutions in view of, among other things, socio-demographic changes caused by the arrival of newcomers. The study, now in progress, is already concerned with the potential clientele for the alternative health services that would be integrated into what is regarded as officiai medicine. Our research project, entitled "Nouveaux arrivants et pathologies émergentes en milieu franco-manitobain: Quelles exigences?" seeks to identify newcomers' implicit (unexpressed) and explicit (known) demands regarding sociocultural and health services available in the Franco-Manitoban host community. The first step involves collecting basic data on migration trends and their multidimensional implications at the community level. This article will, therefore, focus on contrasting local social and health services with the direct and indirect demands of newcomers. It will attempt to identify requirements for community, social and institutional development. The abovementioned theoretical considerations relate to the issues, objectives and approach of our research project. The preliminary data consist of information obtained from Accueil francophone and from several immigrants, such as the excerpt at the beginning of this paper.

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 2 – Inventaire des services de santé disponibles en français et identification des déficits de services - de Moissac, Danielle; Ba, Halimatou; Gagné, Maryanne; Éthier, Sophie (Conseil communauté en santé du Manitoba, 2012)
Au Manitoba, des services de santé en français sont disponibles à Winnipeg, et plus précisément à Saint-Boniface et à Saint-Vital, où habite une forte concentration de francophones. L’objectif de ce deuxième volet de recherche sur l’accès des personnes âgées aux services de santé en français est de dresser un inventaire représentatif des services de santé publics, privés à but lucratif, privés à but non lucratif ou communautaires disponibles en français dans ces deux quartiers, pour ensuite identifier les déficits de services. On définit ici la disponibilité comme étant un service dont peuvent disposer les aînés et qui peut être utilisé par quiconque en fait la demande. Cet inventaire permettra de mieux connaître le nombre, le type et la nature des services existants et de déterminer si tous les services de santé et services sociaux disponibles en français sont répertoriés, soit dans l’Annuaire des services en français de la Société franco-manitobaine. Ceci est important, car une plus grande visibilité des services disponibles en français contribue grandement à leur utilisation par les aînés francophones et leurs aidants lorsque le besoin survient. De plus, l’inventaire permettra d’identifier le type et la nature des services manquants auxquels la population vieillissante pourrait avoir recours.

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

Insight into Post-Pandemic Needs in Healthcare and Well-Being Among Francophone Families in the Canadian Prairies - Keough, Catelyn; Turgeon, Marianne; Proulx-Cullen, Elyse; Leis, Anne; De Moissac, Danielle; Marchak, Kristan; Gnidehou, Sedami (International Journal of Environmental Research and Public Health, 2026)
Francophone populations outside Quebec were disproportionately affected by the COVID-19 crisis. Despite French being one of Canada’s official languages, access to information and services in French remains limited. This study examined Francophone families’ (FF) post-pandemic health and well-being needs (PPHW) in the Canadian Prairie provinces. An online survey assessed PPHW needs among 319 FF in Alberta (AB), Saskatchewan (SK), and Manitoba (MB). Respondents ranked PPHW needs from a predefined list; logistic regression analyzed socio-demographic influences. Divided into AB/SK and MB cohorts, sociodemographic profiles were statistically distinct for many variables, but with similarities found in gender of respondents (women: 73% in AB/SK, 79% in MB), marital status (married: 81% in AB/SK, 88% in MB), area of residence (urban: 86% in AB/SK, 81% in MB), and number of children (2 children: 49% in AB/SK, 41% in MB). Three high-priority needs were shared across provinces: (1) access to recreational, athletic, and artistic activities in French for children (variations by child gender); (2) access to French healthcare professionals (variations by education level and language difference); and (3) social activities in French for families. AB/SK respondents prioritized mental health services in French for adults and youth. MB families prioritized belonging to a Francophone community (variations by gender of children) and education services in French (variations by age of children). Understanding these common and province-specific priorities can inform policy and service planning.